Spelling Tartessian (Palaeohispanica. Revista sobre lenguas y culturas de la Hispania Antigua, 2021)
This paper examines the consonant groups attested in Tartessian or the language of the South-western inscriptions. A comparison with Celtiberian spelling strategies leads to the question how Tartessian could write groups beginning with a stop, if they existed.